FENOMENA PEMBELAJARAN JARAK JAUH PADA MATA PELAJARAN PENDIDIKAN JASMANI, OLAHRAGA, DAN KESEHATAN DI INDONESIA - Rivan Saghita Pratama (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2021)
Education in Indonesia is currently undergoing major changes due to the spread of Covid-19. One of the government's steps to suppress the spread of Covid-19 is to establish a policy of Large-Scale Social Restrictions (PSBB) and PPKM (Enforcement of Restrictions on Community Activities), which have an impact on all sectors of human life, including the education sector. The COVID-19 pandemic has disrupted the face-to-face learning process. Now, the learning process is carried out online, including the practice of sports learning. The purpose of this study is to describe and describe the effectiveness of distance learning on the practice of teaching and learning sports. This research uses exploratory descriptive method. And the technique of collecting information (data analysis) used in this research is the technique of observation and literature study. The results showed that in practical learning on the subjects of Physical Education and Sports, so that the learning process can run in accordance with the achievements, it can be done by using learning media with mobile learning. Where mobile learning is a learning method related to the use of mobile devices such as mobile phones, laptops, tablets, and PCs. Mobile learning is suitable for this online learning. Because by using mobile learning, students can see materials from Physical Education and Sports, and have an overview of the material.